Endosonographic Findings and the Natural Course of Chronic Gastric Anisakiasis: A Single-Center Experience - Eun Young Park; Dong Hoon Baek; Gwang Ha Kim; Bong Eun Lee; So-Jeong Lee; Do Youn Park (Gastroenterology Research and Practice)
Background. Chronic gastric anisakiasis is a rare, usually asymptomatic, and difficult to diagnose infection incidentally discovered during endoscopy, resembling a subepithelial tumor (SET). Because its endoscopic ultrasonography (EUS) findings are not established, it is occasionally misdiagnosed as gastrointestinal mesenchymal tumors and removed by endoscopic or surgical resection. We aimed to assess the characteristic EUS findings of chronic gastric anisakiasis and the clinical course during follow-up. Methods. The database of all patients who underwent EUS at Pusan National University Hospital (Busan, Korea) between January 2011 and December 2016 was retrospectively analyzed. A total of 28 SET cases with EUS features suggesting chronic gastric anisakiasis were included in the study. The EUS, histopathologic, and follow-up endoscopic features were analyzed. Results. On EUS, the lesions were mainly located in the submucosal and/or propria muscle layers. Twenty-seven lesions (27/28, 96%) showed hypoechoic echogenicity, and 22 lesions (22/28, 79%) were heterogeneous. Hyperechoic tubular structures suggesting denaturalized Anisakidae larvae were seen in 22 lesions (22/28, 79%). Endoscopic biopsies revealed significant eosinophil infiltration (≥30 per high-power field) in 12 lesions (12/21, 57%). During the median follow-up period of 9 months (range, 1–55 months), SETs decreased or subsided in 26 lesions (26/28, 93%) with no change in the size of the two lesions (2/28, 7%). Conclusions. Chronic gastric anisakiasis, although rare, should be included in the differential diagnoses for gastric SETs, especially in regions where raw fish is widely consumed. EUS findings suggesting chronic gastric anisakiasis are heterogeneously hypoechoic lesions with hyperechoic tubular structures, mainly in the submucosal and/or muscularis propria layers. Because chronic gastric anisakiasis decreases or subsides in most cases, follow-up endoscopy 6–12 months later is recommended.